Tree diversity at Payeh Maga Montane Forest, Sarawak, Borneo - Kueh, Roland Jui Heng; Mang, Nixon Girang; Ong, Kian Huat; Sait, Muaish; Sam, Sylvester; Empin, George Bala; Rajanoran, Thashwini; Sinus, Cassy Rechie (Institute for Tropical Biology and Conservation, Universiti Malaysia Sabah, 2017)
Tree species composition and diversity were determined at 1,600 m Payeh Maga Highland in Lawas, Sarawak, Borneo. Five study plots (20 x 20 m) were established at five transect lines (1 ha). The study shows that the forest was represented by 40 families, 68 genera and 151 species. Fagaceae represented 26 % of the families recorded, followed by Myrtaceae (16 %) and Clusiaceae (12 %) which are a typical family of montane forest in this region. Important Value Index (IV) showed Lithocarpus urceolaris as the most important species (IV=294 %), followed by Gymnostoma sumatranum (IV=273 %) and Tristaniopsis microcarpa (IV=194 %). There are no significant differences among transects for number of species and diversity indices. This forest is important for biodiversity conservation as it is as rich as those reported for lowland forests elsewhere in this region. The continued accumulation of species is an indication that this highland could support and provide habitat for larger tree species communities.